2004
DOI: 10.1086/423902
|View full text |Cite
|
Sign up to set email alerts
|

Beckwith-Wiedemann Syndrome and IVF: A Case-Control Study

Abstract: A family of human Y chromosomes has dispersed throughout northern Eurasia despite a 1.8-Mb deletion in the azoospermia factor c region. Gen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
214
0
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 347 publications
(225 citation statements)
references
References 21 publications
2
214
0
8
Order By: Relevance
“…It is well know that BWS is more common among patients conceived by artificial reproduction technique; [36][37][38] we encountered a 4.4% prevalence of this phenomenon, confirming data from previous reports and showing a higher prevalence than that reported in the Italian population (1.7%). 39 As concerns tumor risk, the overall prevalence of cancer approximates 8%, consistent with other studies.…”
Section: Phenotypes In Beckwith-wiedemann Syndromesupporting
confidence: 91%
“…It is well know that BWS is more common among patients conceived by artificial reproduction technique; [36][37][38] we encountered a 4.4% prevalence of this phenomenon, confirming data from previous reports and showing a higher prevalence than that reported in the Italian population (1.7%). 39 As concerns tumor risk, the overall prevalence of cancer approximates 8%, consistent with other studies.…”
Section: Phenotypes In Beckwith-wiedemann Syndromesupporting
confidence: 91%
“…89,90 A number of studies report that BWS and AS cases are overrepresented in children born through ART. 42,[91][92][93][94][95] However, other studies did not find evidence for increased risk for these diseases, 96,97 and the relationship between ART and imprinting disorders remains to be established. 98,99 Recently, it was reported that the expression state of the imprinted Dlk1-Dio3 cluster on mouse chromosome 12 is often altered in iPS cells.…”
Section: Molar Pregnancy Infertility Assisted Reproductive Technolomentioning
confidence: 96%
“…46 It is clear that, in the presence of IVF and ICSI, there is an increased risk of the ones caused primarily by epigenetic errors rather than chromosomal problems, such as the case with Beckwith-Weideman syndrome. 47,48 The risk, albeit small, is important because it demonstrates the possibility of other, as yet unidentified, adverse outcomes due to epigenetic errors. Importantly in the context of this review, it does not appear to be an ICSI specific, and therefore, potentially male infertility-related, problem.…”
Section: Overall Defectsmentioning
confidence: 99%